ESG ratings of ESG index providers - Sonakshi Agrawal; Lisa Yao Liu; Shivaram Rajgopal; Suhas A. Sridharan; Yifan Yan; Teri Lombardi Yohn (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2025)
We explore the role of ESG raters' business models in the production of their ratings, noting that increasingly ESG raters not only produce ESG ratings but also construct and sell index products based on their ESG ratings. We examine whether deriving revenue from ESG rating-based indices is associated with inflated ESG ratings for firms with higher stock returns. Consistent with this notion, we find that raters with strong index licensing incentives issue higher ESG ratings for firms with better stock return performance and those added to their ESG indices, compared to raters with weaker licensing incentives. By comparing ESG ratings for a firm across raters with high versus low index licensing incentives, we control for the firm's fundamental ESG performance. We find that the results hold after accounting for different rating methodologies. Overall, our findings suggest that ESG ratings are associated with index construction incentives, highlighting the need for greater transparency in the incentives of producers of ESG ratings.
Keywords: G24; M14; M40; M41; M48; Q56; 330; ESG; index providers; rating agencies; sustainability; disclosure